2013
DOI: 10.1016/j.jaci.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of genome-wide association studies for serum total IgE in diverse study populations

Abstract: Background Immunoglobulin E (IgE) is both a marker and mediator of allergic inflammation. Despite reported differences in serum total IgE levels by race-ethnicity, African American and Latino individuals have not been well represented in genetic studies of total IgE. Objective To identify the genetic predictors of serum total IgE levels. Methods We used genome wide association (GWA) data from 4,292 individuals (2,469 African Americans, 1,564 European Americans, and 259 Latinos) in the EVE Asthma Genetics C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…Although this region was already known to contain genes that influence IgE levels, 10, 11, 13 in this study we identified an important role of local genetic ancestry. In addition, our genome-wide significant associations are different from those previously described in GWAS involving European populations 10,11,13 or Asian populations. 14 Moreover, for the first time we implicated variation in HLA-DQA1 in affecting IgE levels.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Although this region was already known to contain genes that influence IgE levels, 10, 11, 13 in this study we identified an important role of local genetic ancestry. In addition, our genome-wide significant associations are different from those previously described in GWAS involving European populations 10,11,13 or Asian populations. 14 Moreover, for the first time we implicated variation in HLA-DQA1 in affecting IgE levels.…”
Section: Discussionmentioning
confidence: 70%
“…13,26 African American studies included the Study of Asthma Phenotypes and Pharmacogenomic Interactions by Race-ethnicity (SAPPHIRE), the Genetic Research on Asthma in the African Diaspora in African American individuals (GRAAD-AA) and in Afro-Caribbean from Barbados (GRAAD-AC), and the Chicago Asthma Genetics study, Collaborative Studies on the Genetics of Asthma, and Severe Asthma Research Program (CAG/CSGA/SARP). European American studies with measured IgE included the Childhood Asthma Management Program (CAMP), the Childhood Asthma Research and Education Network (CARE), and CAG/CSGA/SARP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from several independent genome-wide association studies (GWAS) lend further support to the involvement of HLA-II loci in asthma, allergic sensitisation and increased total IgE level [4][5][6][7][8][9][10][11]. The GABRIEL consortium carried out the largest asthma GWAS to date, by genotyping 10 365 asthma patients and 16 110 controls recruited from 23 studies [4].…”
Section: Introductionmentioning
confidence: 97%
“…Analysis of data collected within the EVE Consortium revealed ten unique regions associated with serum IgE levels, with the SNP rs9469220 within HLA-DQB1 being most strongly associated. 47 This variant in the MHC locus showed association in all three ethnic groups studied in the EVE Consortium (Caucasian, African American, Latino). A recent report examined both total IgE levels and dust mite-specific IgE in a Korean population.…”
mentioning
confidence: 93%